Effect of Al3Zr Dispersoid on Microstructure and Mechanical Properties of Al-Cu-Li Alloy During Composite Spinning-Extrusion Forming - Zhang, Jin; Zeng, Huaqiang; Wang, Cheng; Tang, Zibo (Frontiers in Materials, 2022)
The regulation of blank microstructure is the key to manufacturing high-quality ring cylinder by composite spinning - extrusion forming. In this paper, the precipitation morphologies of three Al3Zr dispersions were obtained by changing the heat treatment process, and their effects on the microstructure and mechanical properties of Al-Cu-Li alloy ring cylinder were investigated. The results show that the microstructure and mechanical properties of ring cylinder are affected by the different precipitation distribution of Al3Zr dispersoids in the blank. When the Al3Zr dispersoids precipitated and dispersed, the cracking of ring cylinder was eliminated, the thickness of coarse-grained layer decreases obviously, and the elongation is increased by 33.5%. In the T83 state, the average length of the T1 phase decreased from 100.3 to 77.5 nm, while the tensile strength and yield strength of ring cylinder increased by 16 MPa and 20 MPa, respectively.